ความสัมพันธ์ระหว่างภาวะผู้นำแบบท้าทายของผู้บริหารกับองค์กรสมรรถนะสูงของสถานศึกษา กลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร - อาทะวงค์, จิตาภา; กิตติฐานัส, กฤษฎิ์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 1 (2567): มกราคม – เมษายน 2567, 2023)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาระดับของภาวะผู้นำแบบท้าทายของผู้บริหารสถานศึกษา กลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร 2) เพื่อศึกษาระดับขององค์กรสมรรถนะสูงของสถานศึกษา กลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร 3) เพื่อศึกษาความสัมพันธ์ระหว่างภาวะผู้นำแบบท้าทายของผู้บริหารกับองค์กรสมรรถนะสูงของสถานศึกษา กลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร กลุ่มตัวอย่าง ได้แก่ ครู กลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร จำนวน 350 คน เครื่องมือที่ใช้เก็บรวบรวมข้อมูล คือ แบบสอบถาม การวิเคราะห์ข้อมูลโดยใช้โปรแกรมสำเร็จรูปทางสถิติด้วยการหาค่าความถี่ ค่าร้อยละ ค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐาน ทดสอบความสัมพันธ์ระว่างตัวแปรด้วยวิธีของของเพียร์สัน               ผลการวิจัยพบว่า 1) ภาวะผู้นำแบบท้าทายของผู้บริหารสถานศึกษา กลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร โดยภาพรวมมีค่าเฉลี่ยอยู่ในระดับมาก ด้านที่มีค่าเฉลี่ยสูงสุด คือ ด้านการเสริมสร้างกำลังใจ รองลงมา ได้แก่ ด้านการเปิดโอกาสให้คนอื่นได้ปฏิบัติ ส่วนด้านการสร้างแรงบันดาลใจในการวิสัยทัศน์ร่วมกัน มีค่าเฉลี่ยต่ำสุด 2) องค์กรสมรรถนะสูงของสถานศึกษา กลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร โดยภาพรวมมีค่าเฉลี่ยอยู่ในระดับมาก ด้านที่มีค่าเฉลี่ยสูงสุด คือ ด้านการสื่อสารอย่างเปิดเผยระหว่างบุคลากรในองค์กร รองลงมา ได้แก่ ด้านการเรียนรู้อย่างต่อเนื่อง ส่วนด้านการแบ่งปันอำนาจและการมีส่วนร่วม มีค่าเฉลี่ยต่ำสุด 3) ภาวะผู้นำแบบท้าทายของผู้บริหาร มีความสัมพันธ์เชิงบวกในระดับสูงกับองค์กรสมรรถนะสูงของสถานศึกษากลุ่มกรุงธนใต้ สังกัดกรุงเทพมหานคร อย่างมีนัยสำคัญทางสถิติที่ระดับ .01                The objectives of this research are 1) to study the level of challenging leadership of school administrators in the Southern Krungthon Group under the Bangkok Metropolitan Administration, 2) to study the level of high organizational capacity of schools in the Southern Krungthon Group under the Bangkok Metropolitan Administration, and 3) to examine the relationship between challenging leadership of school administrators and high organizational capacity of schools in the Southern Krungthon Group under the Bangkok Metropolitan Administration. The sample group consisted of 350 teachers in schools in the Southern Krungthon Group under the Bangkok Metropolitan Administration. Data were collected through questionnaires and analyzed using statistical software to find frequencies, percentages, averages, and standard deviations, as well as to test the correlation between variables using Pearson's correlation.            The research findings indicate that: 1) The challenging leadership of school administrators in the Southern Krungthon Group under the Bangkok Metropolitan Administration is at a high level overall. The highest average score is related to empowering and motivating, followed by giving opportunities for others to perform, while the lowest average score is related to creating a shared vision and inspiration in visioning together. 2) The high organizational capacity of schools in the Southern Krungthon Group under the Bangkok Metropolitan Administration is at a high level overall. The highest average score is related to communication openness among staff in the organization, followed by continuous learning, while the lowest average score is related to power sharing and participation. 3) Challenging leadership of school administrators has a positive and statistically significant relationship at the .01 level with the high organizational capacity of schools in the Southern Krungthon Group under the Bangkok Metropolitan Administration.